A study regarding the availability and utilization of water supply and sanitation practices in rural Amritsar, Punjab, India - Bakshi, Ritika; Singh, Tejbir; Kaur, Jasleen; Arora, Ankit; Verma, Richa (International Journal of Research in Medical Sciences, 2019)
Background: Access to safe water and sanitation practices is an important issue of health and development at local, regional and national levels. The government has come up with various facilities regarding the water supply and sanitation but there are various factors which curtail their utilization. The present study deals with the extent of utilization and factors impeding the utilization of such services at the village level. Methods: The present impeding cross-sectional study was carried out in village Nagkalan, Amritsar, where the eldest adult member present in the house at the time of the visit was interviewed. Every house of the village was visited during the period of January 2017 to December 2017, and a total of 1123 families were included in the final analysis. Thereafter, data was compiled and analyzed. Results: Out of total 1123 families, only 31.4% were using government water supply (tap water); while 42.7% had no government connection at all and used submersible as their sole source of water supply. 20.2% did not have a toilet at their house and therefore practiced open defecation; out of which majority families belonged to lower socio-economic status (statistically significant). Out of total 896 families having a toilet at their house, there were only 30 families (3.4%) who responded that some of the family members practice open defecation. Also, only 6.1% of the respondents were aware about the functions of Village Health Sanitation and Nutrition Committee (VHSNC). Conclusions: More number of families (42.7%) were dependent on submersible pump as sole source of water supply. 20.2% lacked separate toilet facility, mostly belonging to lower socio- economic status. Only 6.1% were aware regarding the VHSNC. All the families disposed of their household waste on the roads.